Accurate and Sensitive Analytical Method for the Determination of Cyclanilide in Cotton and Cosmetic Pads at Trace Levels Using the Combination of Vortex Assisted Iron(II, III)/Reduced Graphene Oxide Nanocomposite Based Dispersive Solid Phase Extraction and High Performance Liquid Chromatography (HPLC). (21st September 2020) - Erarpat, Sezin; Maltepe, Esra; Öztürk Er, Elif; Bakırdere, Sezgin
Abstract: A novel, accurate and sensitive analytical method was developed to determine cyclanilide using vortex assisted Fe3 O4 /reduced graphene oxide nanocomposite based dispersive solid phase extraction by high performance liquid chromatography (HPLC). An iron (II, III)/reduced graphene oxide nanocomposite (Fe3 O4 /rGO) was employed to extract and separate cyclanilide from aqueous solution. After the optimization of HPLC system, important parameters for the extraction method including mass of Fe3 O4 /rGO, pH, volume of buffer solution, nature/volume of eluent solution and vortex period were examined to obtain the highest extraction yields. Under the optimum conditions, the enhancement in the detection power was found to be 35-fold by the developed method. The limits of detection and quantification of the proposed method were 2.6 and 8.7 ng g −1, respectively. In order to characterize the accuracy and applicability of developed method, recovery studies were performed upon cotton and cosmetic pads. High percent recovery results between 90 and 104% were obtained for cotton and cosmetic pad samples. Therefore; this method may be easily applied to cotton samples with excellent precision and accuracy.